PENGARUH FOOD QUALITY, SERVICE QUALITY DAN PRICE FAIRNESS TERHADAP REPATRONAGE INTENTION YANG DIMEDIASI OLEH CUSTOMER SATISFACTION PADA KANTIN MAKANAN JEPANG HANA DI BANDA ACEH - Nabila Masarrah Harsha; M Ridha Siregar (Departemen Manajemen, 2020)
Abstract: This study aims to measure the effect of Food Quality, Service Quality and Price Fairness to Repatronage Intention with Customer Satisfaction as a mediating variable at the Restaurant Kantin Makanan Jepang Hana. The sample used in this study was customer of Restaurant Kantin Makanan Jepang Hana involving 190 respondens. Instrument used for data collecting was questionnaire. Convenience sampling was used as sampling technique. Partial Least Square (PLS) was used as analysis method to determine the effect of variables involved. Based on the analysis results, it is indicated that Food Quality, Service Quality and Price Fairness influence Customer Satisfaction, Customer Satisfaction influence Repatronage Intention, Customer Satisfaction partially mediate the relationship betweens Food Quality, Service Quality and Price Fairness to Repatronage Intention.